(untitled) (Research, Society and Development, 2022)
Objective: To survey the scientific knowledge regarding nursing care actions in patients using an artificial pacemaker. Methodology: This is an integrative literature review with a qualitative approach by thematic analysis technique. Results and discussions: a final sample of six articles was obtained through the search strategies in the databases and through the thematic analysis technique, the most addressed categories were perioperative nursing care (pre-, trans- and postoperative) and the nurse as a health educator. Final considerations: nursing care was predominantly based on perioperative care, where theoretical and practical knowledge was highlighted, in addition to the use of nursing care systematization, through the nursing process, as a tool to plan interventions. Another aspect to be considered was the role of nurses as health educators, where it is evident the importance of this professional in the context of assistance in pacemaker implantation.